A survey of ICU professional nurses' knowledge of blood glucose physiology and blood glucose control in critically ill adult patients in a public tertiary hospital in the Western Cape Province - Mesela, Monwabisi Charles (Division of Nursing and Midwifery, 2015)
Blood glucose control with intravenous insulin therapy is one of the most frequently used treatment modalities to manage hyperglycaemia in critically ill patients. Almost all critically ill patients admitted in the Intensive Care Unit (ICU) will require blood glucose control to manage stress induced hyperglycaemia. Blood glucose control by means of intravenous insulin therapy is associated with reduced morbidity and mortality rates, which ultimately improves patient care outcomes. Although blood glucose control is beneficial for critically ill patients, however, it is potentially dangerous due to the side effects of insulin therapy, namely hypoglycaemia and hypokalaemia. As ICU professional nurses are responsible for blood glucose control in critically ill patients, it is therefore essential that they have adequate knowledge of blood glucose control measures to ensure patient safety and improve outcomes. The aim of this study was to determine ICU professional nurses’ knowledge of blood glucose physiology and blood glucose control in critically ill adult patients in a public tertiary hospital in the Western Cape Province. The study was non-experimental, descriptive and quantitative in nature. Data was collected by means of an anonymous, self-administered questionnaire in June 2013. Ethical approval to conduct the study was obtained from the University of Cape Town’s Health Sciences Faculty Human Research Ethics Committee. Permission to conduct the study in the specific research setting was obtained from the Hospital Senior Medical Services Manager. Descriptive and correlational statistics were used to analyse the data.